Gut IgA abundance in adult life is a major determinant of resistance to dextran sodium sulfate‐colitis and can compensate for the effects of inadequate maternal IgA received by neonates - Gupta, Suman (Immunology, 2019)
Studies with gene‐deficient and gnotobiotic mice have identified many host and microbial factors that contribute to induced colitis, but information on whether specific factors determine susceptibility under more physiological conditions is lacking. Using wild‐type strains that differ in their IgA response but harbor a diverse gut microbiome, we found that the IgA‐high strain CBA/CaJ (CBA) is resistant to acute colitis induced with dextran sodium sulfate (DSS), unlike the IgA‐low strain C57BL/6 (B6). Resistance was associated with extensive IgA‐coating of fecal bacteria, lower fecal bacterial loads and greater abundance of barrier‐protective transcripts in colonic tissues under homeostatic conditions. Fecal microbial transplant (FT) experiments revealed that disease induction in B6 mice was associated with a cohort of bacteria that are not targeted by IgA. However, CBA mice continued to be resistant to colitis induction following FTs from B6 mice, indicating that they are able to contain such colitogenic members. In support of a role for bacterial exclusion in resistance, oral administration of immunoglobulins decreased DSS‐induced disease in B6 mice. In F(1) mice derived separately with CBA and B6 dams and in F(1) mice backcrossed to the two parental strains, resistance segregated with the IgA response of the pups and not with barrier‐associated transcripts or bacterial loads. Interestingly, B6 pups foster‐nursed on CBA dams continued to be susceptible in later life, whereas CBA pups foster‐nursed on B6 dams continued to be resistant. Together, the data indicate that a high‐IgA response in adult life can protect against colitis and compensate for IgA deficiency in early life.